Invasion biology of the cotton mealybug, Phenacoccus solenopsis Tinsley: Current knowledge and future directions - Hao-jie TONG; Yan AO; Zi-hao LI; Ying WANG; Ming-xing JIANG (Journal of Integrative Agriculture, 2019)
The cotton mealybug Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae), which is native to North America, emerged as a major invasive insect pest of multiple crops in Asia at the beginning of the 21st century. Considering the economic significance of this insect and its rapid worldwide spread, we examined the possible factors driving its invasions. In this paper, we summarize the life history traits of P. solenopsis conceivably related to population development in invaded regions; these traits include its use of diverse host plants, reproductive capacity and mode, adaptation to temperature, response to food shortage, and insecticidal resistance. Then, focusing on the multiple trophic interactions that may promote or hinder invasion, we review the mutualistic relationship of this mealybug with ants and predation and parasitism by natural enemies. Finally, we suggest topics for future research and provide our perspective on the biological invasions of this mealybug. We speculate that specific biological factors associated with this mealybug, particularly its wide host range, high reproductive potential, evolved changes in life history traits, and mutualism with ants have played important roles in its invasions, allowing this pest to become established and rapidly increase its population upon its introduction into new regions.